Base layer construction rammer compactor - SANG LUHUA; HUANG XINXIA (2014)
The utility model relates to a base layer construction rammer compactor which comprises a case. A motor is fixedly connected into the case. The lower end of the case is provided with an opening. A rammer is arranged on the opening of the lower end of the case. The side wall of the case is fixedly connected with an LED used for illuminating. The portion, above the LED, of the side wall of the case is fixedly connected with a lampshade used for preventing illumination dazzling of the LED and water. The lower surface of the case is fixedly connected with a dustproof cover used for preventing dust from being raised in the working process of the rammer. The upper end of the case is fixedly connected with a power source device used for supplying power to the motor and the LED. The upper end of the power source device is provided with a control switch corresponding to the motor and the LED. According to the base layer construction rammer compactor, an illuminating device is arranged on the outer side, a dustproof device is arranged on the bottom, and therefore the rammer compactor can work normally and conveniently under the circumstance of insufficient light, and can be prevented from generating a great deal of raised dust in the working process.